An Empirical Study of Critical Soft Factors for Quality Improvement in The Electrical and Electronics Firms in Malaysia - Muhammad Madi Abdullah (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2006)
Soft factors are important aspect that sustains the organizations in their efforts towards continuous quality improvement (QI) and customer satisfaction. The conventional wisdom states that quality improvement in organizations increases profits and productivity. Therefore, the aim of the paper is to examine the influence of critical soft factors (CSF) on quality improvement (QI). For that purpose, this study examine: (i) the relationship between the CSF and QI and (ii) to what extent the six CSF explain QI. The study used survey data from 255 electrical and electronics (E&E) firms in Malaysia. The individual managers representing the each firm made the unit of analysis of the study. The finding reveals that QI was significantly influenced by the following soft factors: management commitment, customer focus, employee involvement, training & education, and reward & recognition. Supplier relationship was not a significant predictor of quality improvement. Finally, this study has empirically shown that quality improvement will increase when the organizations emphasize more on soft factors.Keywords: Critical soft factors, quality improvement, Electrical and Electronics firms